CHARGE-DISTRIBUTION IN (TL,PB)SR2CA2CU3O9-DELTA(T-C=124K) - AN O-17 NMR-STUDY - Han, Z; Dupree, R; Howes, A; Liu, R; Edwards, P (1994)
17O NMR measurements on (Tl,Pb)Sr2Ca2Cu3O9-σ (Tc=124K) show that the Knight shift of the outer two Cu-O planes (with pyramidal coordination for copper) has a very different behavior to that of the inner plane (with square coordination for copper). The former has a larger magnitude and a weaker temperature dependence in the normal state, whereas the latter is smaller but has a stronger temperature dependence, implying a nonhomogeneous charge distribution and a weak interaction among the Cu-O layers. The results are compared with those for (Bi,Pb)2Sr2Ca2Cu3O10-σ (Tc=107K) and Tl2Ba2Ca2Cu3O10-σ (Tc=125K). © 1994.